Validation of Immersion Precooling and Drip Sanitation Standard Operating Procedures on Weight, Temperature, Microbiological Quality, and Safety of Chicken Carcasses - Angela B.P.S. Fernandes; Clair F.S. Pereira; Hiago M. Pereira; Marco A.C. Batista; Luiz F.S. Dionisio; Amauri A. Alfieri; Bruna Alexandrino; José C. Ribeiro-Júnior (Journal of Food Protection)
This study aims to validate sanitation standard operating procedures (SSOPs) of the precooling system in two immersion stages with different temperatures followed by dripping for 3 min. The variables evaluated were temperature, weight, microbiological quality, and safety of chicken carcasses. Groups of indicator microorganisms were quantified and the occurrence of Salmonella spp., Listeria monocytogenes, diarrheagenic Escherichia coli (non-157), and Staphylococcus aureus with enterotoxigenic potential was investigated, before and after cooling by immersion and dripping. Salmonella serovars were determined by real-time PCR. Immersion of the carcasses in water at 9.5 (±2.89) and 2.33 (±1.30) °C in the first and second stages was sufficient to considerably reduce the carcass temperature to 5.70 and 7.41 °C at the system outlet and after dripping, respectively. The weight gain was 5.5%, in accordance with Brazilian legislation (<8%). Immersion cooling significantly reduced (p < 0.05) the total counts of enterobacteria, total coliforms, and E. coli. Contamination was reduced in the carcasses, which increased the water counts in the system to 3.76 log CFU/mL for psychrotrophs. Salmonella spp. was identified in 100% of the carcasses evaluated and in the water from the first and second stages of cooling. The main serovars were S. Newport and S. Minnesota. Pathotypes of diarrheagenic E. coli, mainly atypical EPEC and STEC, and S. aureus with enterotoxigenic potential were highly prevalent in the carcasses even before entering the precooling systems by immersion, which was not sufficient to rule out the occurrence of any pathogen studied. Despite the notable SSOP effect on the quantification of microbiological indicators during immersion cooling, the high occurrence of different pathogens underlies the need to review procedures and techniques not only in slaughterhouses but also throughout the production chain, acting in an integrated manner to provide biosecurity and reduce risks to the consumption of chicken meat.